The evaluation process in Advanced Artistic Education - Checa Jódar, Rodrigo (Avances en Supervisión Educativa, 2022)
Higher Artistic Education has been the subject of a profound review since its integration into the educational system. The LOGSE (1990) promoted for the first time the creation of a higher degree of variable duration with qualifications equivalent to Bachelor and Master’s Degree. The LOE (2006) introduced these teachings in higher education and established that their design would be carried out within the framework of higher education, which implies the obligation to establish quality assurance procedures for higher artistic education. For this, it is necessary to make it clear the situation of these teachings in the current configuration of the educational system and the designation of the institution with competences for the evaluation of centers and programs. After an analysis of the regulations that must be applied to these teachings and the centers that impart them, it is concluded that the Inspectorate of Education becomes a quality factor to guarantee their quality, not only from a normative point of view, but also because of the qualification and professionalization itself of education inspectors.
Keywords: higher education; advanced artistic education; evaluation; inspectorate of education; conservatory of music; european space of higher education; music; dancing; dramatic art; design